2022
DOI: 10.1097/rlu.0000000000004488
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT and 68Ga-DOTA-FAPI-04 PET/CT Findings of Myeloid Sarcoma

Abstract: A 28-year-old woman presented with a 2-month history of swelling and pain in the chest wall. An irregular soft tissue mass in the chest wall and mediastinum was showed on chest CT. 18F-FDG PET/CT revealed obvious FDG uptake in the mass. Subsequently, the patient was participated in a 68Ga-DOTA-FAPI-04 PET/CT tumor clinical trial. 68Ga-DOTA-FAPI-04 PET/CT also showed elevated tracer uptake in the mass. Biopsy of the mass confirmed a diagnosis of myeloid sarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…21 Several case reports have shown that 68 Ga-FAPI is superior to 18 F-FDG in myeloid sarcoma imaging, which needs to be further validated in larger studies. 22 The typical imaging findings of bone myeloid sarcoma are destructive skeletal lesions and soft tissue masses, with clinical manifestations of pain and abnormal movement of the affected area. 23 Our patient presented with increased bone mineral density with increased FDG uptake in the right humerus without bone destruction or soft tissue mass formation, which is a rare finding and expands the imaging features of bone myeloid sarcoma on PET/CT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Several case reports have shown that 68 Ga-FAPI is superior to 18 F-FDG in myeloid sarcoma imaging, which needs to be further validated in larger studies. 22 The typical imaging findings of bone myeloid sarcoma are destructive skeletal lesions and soft tissue masses, with clinical manifestations of pain and abnormal movement of the affected area. 23 Our patient presented with increased bone mineral density with increased FDG uptake in the right humerus without bone destruction or soft tissue mass formation, which is a rare finding and expands the imaging features of bone myeloid sarcoma on PET/CT.…”
mentioning
confidence: 99%
“…Myeloid sarcoma has moderate FDG uptake due to increased glycolytic activity with SUV max in the range of 2.6 to 9.7 21 . Several case reports have shown that 68 Ga-FAPI is superior to 18 F-FDG in myeloid sarcoma imaging, which needs to be further validated in larger studies 22 . The typical imaging findings of bone myeloid sarcoma are destructive skeletal lesions and soft tissue masses, with clinical manifestations of pain and abnormal movement of the affected area 23 .…”
mentioning
confidence: 99%